STUDIES ON INTERFERENCE AMONG TREES IN A PLANTATION OF ALTINGIA EXCELSA - SAKAI, KAN-ICHI (BIOTROPIA, 2024)
AÂ studyÂ was made withÂ theÂ useÂ ofÂ aÂ 50-yearÂ oldÂ AltingiaÂ excelsa NoronhaÂ plantation withÂ 260 standing trees for separating components of density and intraspecific competition. A component of density effectÂ causes overall decreaseÂ in growth whileÂ that ofÂ competitionÂ resultsÂ in aÂ contrastingÂ effectÂ in growth between any pair of neighboring trees. To detect this density effect, it is most appropriate to use an area of ca. 100 m2 Â irrespective of the experimental area, e.g. circular or quadratic. Competition effect cannot be detected when two individuals are apart more than two meters. An application of the density and competitive ability to tree breeding is briefly mentioned.